Assessment of available and stable fluoride in four widely-used toothpastes in the Iranian market. - Jaber Yaghini; Sima Kiani; Shiva Mortazavi; Bahareh Haghshenas; Ahmad Mogharehabed (Tehran University of Medical Sciences, 2014)
Presence of available and stable fluoride in a dentifrice formulation is a major requirement for an anti-caries effect. Although the available fluoride concentration in Iranian dentifrices has been reported in previous studies, there is little information on its stability; which is dependent upon dentifrice formulation. This study was done to assess the fluoride ion concentration and stability in four widely used dentifrices in Iran.In this analytical study, three samples of each brand of dentifrice (Nasim, Pooneh, Crest, and Signal) were purchased. Total fluoride (TF) and total soluble fluoride (TSF) concentrations were determined by ion specific electrodes. Data about TF were analyzed by one-way analysis of variance (ANOVA). Kruskal-Wallis and Mann-Whitney tests were used for nonparametric data (TSF).All dentifrices had more than 1000 ppm of fluoride ions. TSF in Crest was significantly higher than in other dentifrices (P